English Teacher's Learning Strategy to Increase Students' Interest in Class (Study at SMP N 22 Tebo Jambi) - Yulia Wiji Astika (Journal Of Language Education and Development (JLed), 2020)
The problem faced in education was the weak learning process. The problem that was often found when the learning process in class was that students do not have an interest in English subjects. The purpose of this study was to find out how the learning strategies of the English teacher in increasing students' interest in learning and to find out the factors that influence students' interest in learning. The method used in this study was descriptive qualitative method. The population in this study was English teacher in class VII.A SMP N 22 Tebo Jambi and students who were in the class. Data collection techniques used by researchers were observation, interviews, and documentation. The result of this study were English teacher’s learning strategies in increasing students’ interest in learning in the class have not been effective. It was showed by the quality of student learning in class VII.A has difficulty in understanding the explanation of the material by the teacher. The suitability of the learning level has not been created, there was no incentive given to the students, and a short time in doing the work. Then, the factors that influence students’ interest in learning were internal, external, and learning approaches.